Educação e controle social: reflexões acerca da coesão interna entre autonomia pública e privada - Salomão, Izabel Cristina Salvador (2009)
This work analyzes the relationship between the level of Brazilian public education and the social participation of its population, as well as the instances of social control of the society by the State, its wounds and the ability to influence public policies, especially educational ones. In this sense, this study points out the constitutional paradigm as a gravitational center for the State-society relations, always supported by the habermasian theory of co-originality and mutual assumption between the citizen’s public and private autonomy. By means of the comprehension of the historical-social formation of the Brazilian public, the study aims at locating the origin of the “privilege culture” and withdrawal from the collective, so embedded in the soul of this “yet to be people”. Evaluating the historical trajectory of popular education, the study was able to identify the deleterious consequences for the democratic state of law and for the participative democracy, as its development, and in the end, reflecting upon the role of the District Attorney's Office in making real the present constitutional paradigm, by clearing the channels of popular participation.